A Case Report of Bowel Perforation in a Gravid COVID-19 Patient - A. T. Guiritan; J. G. Cataluña (Case Reports in Medicine)
Background. Bowel perforation in a pregnant patient with COVID-19 infection is a rarely reported complication. With the uncovering of the different treatment modalities and complications of this disease, this case highlights diagnostic and therapeutic dilemmas and limitations in a special population. Clinical Presentation. A 35-year-old female, Gravida 2 Para 1 at 31 weeks age of gestation (AOG) who underwent cesarean section for nonreassuring fetal status in 2019, was admitted for severe COVID-19 infection presenting with dyspnea. During her hospitalization, she developed progressive dyspnea from worsening of COVID-19 infection. Patient was eventually intubated and was given a total of two doses of tocilizumab, adequate antibiotic treatment, remdesivir, and dexamethasone. An emergency repeat cesarean section was performed due to maternal deterioration and poor variability of the fetus. She delivered to a live preterm baby girl, with an Apgar score of 1 and 7 on the 1st and 5th minute of life respectively. During the postoperative days, patient remained intubated and sedated. Increasing residuals were noted per nasogastric tube (NGT). Serial scout film of the abdomen (SFA) and medical management were performed. Upon weaning from sedation, patient complained of right lower quadrant pain. A whole abdominal computed tomography (CT) scan with contrast was requested which revealed large bowel obstruction. Patient was referred to surgery service. Upon assessment, abdomen was noted to be rigid with guarding during palpation. A scout film of the abdomen was requested and revealed extensive amount of pneumoperitoneum with scanty to absent colonic gas suggestive of bowel perforation. Patient underwent emergency exploratory laparotomy. Upon opening the peritoneum, free air was evacuated. Approximately 1.4 liters of fecaloid peritoneal fluid was suctioned and adhesive band was noted at the pelvic area. A 2 cm full thickness perforation at the cecum with 17 cm serosal tear from the cecum to ascending colon was noted. Bowel loops proximal to the perforation were dilated. Nasogastric tube was inserted for bowel decompression. Right hemicolectomy was performed. Specimen was sent for histopathology. Acute inflammatory cells infiltrating the blood vessels and possible microthrombi and beginning thrombus formation were noted in the subserosa. Patient eventually expired on the 14th hospital day from sepsis. Conclusion. This case highlights a rarely reported complication of COVID-19 infection. Confluence of factors that predisposed the patient include pregnancy, COVID-19 infection, use of tocilizumab, and recent surgery. High index of suspicion is vital in the management and improvement of outcomes.